2015
DOI: 10.1255/ejms.1326
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Protonated 2-(2-Phenylethyl)Chromones from Agarwood: The Diagnostic Role of Ion/Neutral Complexes as Reactive Intermediates

Abstract: A positive-ion electrospray ionisation collision-induced dissociation mass spectrometric study on the fragmentation of the [M + H](+) ions of 2-(2-phenylethyl)chromone and a set of nine hydroxyl- and/or methoxy-substituted derivatives has revealed a highly prominent fragmentation channel, the loss of benzoquinomethanes or a benzaldehyde, respectively, as a diagnostic feature for 2-(2-phenylethyl)chromones that bear a hydroxyl group at the para- (4'-), ortho- (2'-) and/or benzylic (α-) position of the phenyleth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…A specific and diagnostic fragmentation reaction was found during FRIPS of Tyr‐containing peptides, taht is, the loss of C 7 H 6 O (4‐methylenecyclohexa‐2,5‐dienone) with a characteristic mass of 106 u, as rationalized in Figure and discussed by Hopkinson and Siu . Interestingly, the same neutral loss was found in the fragmentation of protonated (2‐phenylethyl)chromones as reported by Kuck et al…”
Section: Fripssupporting
confidence: 69%
“…A specific and diagnostic fragmentation reaction was found during FRIPS of Tyr‐containing peptides, taht is, the loss of C 7 H 6 O (4‐methylenecyclohexa‐2,5‐dienone) with a characteristic mass of 106 u, as rationalized in Figure and discussed by Hopkinson and Siu . Interestingly, the same neutral loss was found in the fragmentation of protonated (2‐phenylethyl)chromones as reported by Kuck et al…”
Section: Fripssupporting
confidence: 69%
“…As reactive intermediates in gas‐phase ionic reactions, ion‐neutral complexes (INCs) are applied to species in which an ion and a neutral are held together mainly by electrostatic attraction. Unimolecular decomposition processes mediated by INCs involve either a direct separation without a significant barrier or further internal ion‐molecule reactions . Obviously, the kinetic and mechanistic role of INCs hinges heavily on their lifetime behaviors .…”
Section: Introductionmentioning
confidence: 99%
“…Benzyl cations are highly reactive intermediates in various chemical and biochemical reactions and usually short‐lived in solution . In an INC, benzyl cations formed during the CID process may lead to hydride transfer, electron transfer, proton transfer, electrophilic aromatic substitution and nucleophilic aromatic substitution …”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40] In an INC, benzyl cations formed during the CID process may lead to hydride transfer, electron transfer, proton transfer, electrophilic aromatic substitution and nucleophilic aromatic substitution. [7,8,11,20,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] In the previous studies, the proton donation ability of the 4-methylbenzyl cation was found to be dramatically enhanced by its methylene arenium character. [20,39] In contrast, the positive charge cannot reside at meta-position of the 3-methylbenzyl cation; therefore, the meta-methyl group cannot react as a proton donor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation